Transformative Dynamics of Youth Involvement in the Just Transition Process: The Case of Active Youths in the Region of Western Macedonia, Greece - Stergiou, Konstantinos; Filippidis, Kostas; Papoutzis, Lazaros; Zourka, Stefania (Archives of Business Research, 2024)
Western Macedonia, a region nestled in the northwestern part of Greece, has long been renowned for its rich natural resources, particularly its abundant coal reserves. Τhe imperative to transition away from coal-related industries has brought to light the need for economic diversification. Western Macedonia’s heavy dependence on coal mining and energy production has left it vulnerable to the inevitable decline of fossil fuels (Ziouzios, Karlopoulos, Fragkos, Vrontitsi, 2021). To secure its future and ensure the well-being of its residents, the region must identify and develop new economic sectors that align with a sustainable, low-carbon future. However, as the global shift towards sustainable energy production gains momentum -and as the climate crisis shows its harsh face-, Western Macedonia has found itself facing a myriad of challenges that have constrained the initiation of a Just Transition process in regions that were dependent on lignite (Vatalis, Avlogiaris, Tsalis 2022). The transition seeks to address critical issues, such as staggering unemployment rates, the significant brain drain of the region, and the need to diversify its economy away from coal-dependent industries.